SPM pathway marker analysis of the brains of obese mice in the absence and presence of eicosapentaenoic acid ethyl esters. (December 2021) - Vander Ploeg, Matthew; Quinn, Kevin; Armstrong, Michael; Manke, Jonathan; Reisdorph, Nichole; Shaikh, Saame Raza
Highlights: The effect of obesity on brain SPM intermediates is unknown. High fat diet does not lower the levels of murine brain SPM intermediates. Eicosapentaenoic acid (EPA) supplementation of a high fat diet increases brain 12-HEPE. EPA supplementation also lowers select circulating n-6 PUFA-derived metabolites. Abstract: Obesity drives an imbalanced signature of specialized pro-resolving mediators (SPM). Herein, we investigated if high fat diet-induced obesity dysregulates the concentration of SPM intermediates in the brains of C57BL/6 J mice. Furthermore, given the benefits of EPA for cardiometabolic diseases, major depression, and cognition, we probed the effect of an EPA supplemented high fat diet on brain SPM intermediates. Mass spectrometry revealed no effect of the high fat diet on PUFA-derived brain metabolites. EPA also did not have an effect on most brain PUFA-derived metabolites except an increase of 12-hydroxyeicosapentaenoic acid (12-HEPE). In contrast, EPA dramatically increased serum HEPEs and lowered several PUFA-derived metabolites. Finally, untargeted mass spectrometry showed no effects of the high fat diet, with or without EPA, on the brain metabolome. Collectively, these results show the murine brain resists a deficiency in SPM pathway markers in response to a high fat diet and that EPA supplementation increases 12-HEPE levels.